Postoperative Urinary Retention. Issue 4 (April 2023) - McDermott, Colleen D.; Tunitsky-Bitton, Elena; Dueñas-Garcia, Omar F.; Willis-Gray, Marcella G.; Cadish, Lauren A.; Edenfield, Autumn; Wang, Rui; Meriwether, Kate; Mueller, Elizabeth R.
Abstract : Abstract: This clinical consensus statement on the management of postoperative (<6 weeks) urinary retention (POUR) reflects statements drafted by content experts from the American Urogynecologic Society's POUR writing group. The writing group used a modified Delphi process to evaluate statements developed from a structured literature search and assessed for consensus. After the definition of POUR was established, a total of 37 statements were assessed in the following 6 categories: (1) incidence of POUR, (2) medications, (3) patient factors, (4) surgical factors, (5) urodynamic testing, and (6) voiding trials. Of the 37 original statements, 34 reached consensus and 3 were omitted.